2013
DOI: 10.1371/journal.pone.0071362
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Histological Response to Chemotherapy in Osteosarcoma Patients Receiving Tumor-Bearing Frozen Autograft

Abstract: BackgroundA variety of surgical procedures are now available for tissue reconstruction after osteosarcoma excision, and an important prognostic factor is the evaluation of response to chemotherapy using histology. Although tumor-bearing autografts are useful tools for reconstruction, re-use of the primary tumor may make it difficult to assess the histological response to chemotherapy, since the entire tumor cannot be analyzed. Here, we analyzed the prognostic value of the histological response in the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
(35 reference statements)
0
28
0
2
Order By: Relevance
“…Pathological evaluations of response to neoadjuvant chemotherapy in case presentations were based on only a part of the tumour: curettage cancellous bone and/or extraskeletal mass; however, we have reported that the histological evaluations of small samples were correlated with the response to chemotherapy and the prognosis [29]. Secondly, comparison between two methods: the free-freezing method and pedicle-freezing method, was not enough to clarify the usefulness of the pedicle-freezing method in terms of bone union or complication of fractures because the patient numbers of each methods were small.…”
Section: Discussionmentioning
confidence: 96%
“…Pathological evaluations of response to neoadjuvant chemotherapy in case presentations were based on only a part of the tumour: curettage cancellous bone and/or extraskeletal mass; however, we have reported that the histological evaluations of small samples were correlated with the response to chemotherapy and the prognosis [29]. Secondly, comparison between two methods: the free-freezing method and pedicle-freezing method, was not enough to clarify the usefulness of the pedicle-freezing method in terms of bone union or complication of fractures because the patient numbers of each methods were small.…”
Section: Discussionmentioning
confidence: 96%
“…However, postoperative recovery is prolonged, full weight bearing ambulation usually being delayed. In addition, postoperative complications, including recurrence, fracture, infection and nonunion, are not negligible [3][4][5][6][7][35][36][37][38] . Mechanical reconstruction can achieve ideal tumor resection margins and allow instant weight bearing ambulation postoperatively.…”
Section: Comparison Of Therapeutic Effects Of Biological and Mechanicmentioning
confidence: 99%
“…Histological response of the surgically removed tumor to pre‐operative chemotherapy represents the most pivotal prognostic factor thus far . Patients with good histological response (necrosis percentage ≥ 90%) may have a better prognosis than those with poor histological response (necrosis percentage < 90%) . Previous investigations have had discrepant results due to the limited number of tissue samples.…”
Section: Discussionmentioning
confidence: 99%